Secondary battery, and battery module, battery pack and power device including same

By using a nonaqueous electrolyte containing lithium hexafluorophosphate and lithium bisfluorosulfonimide in the secondary battery, combined with controlling the thickness and elongation of the positive electrode current collector, the problem of poor performance of the secondary battery after thinning is solved. It achieves both low cost, high energy density and high safety performance.

CN119170859APending Publication Date: 2024-12-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411386760.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

After thinning the positive electrode current collector, it is difficult to take into account low cost, high energy density, high power performance, good processing performance and high safety performance. There are increased internal resistance of the battery, increased heat production and poor processing performance. question.

Method used

Using a nonaqueous electrolyte containing specific compounds, including a combination of lithium hexafluorophosphate and lithium difluorosulfonimide, a low-impedance interface film is formed by controlling the compound content in the nonaqueous electrolyte, the thickness and elongation of the positive electrode current collector. , improve lithium ion transmission and battery safety.

Benefits of technology

The secondary battery is achieved under thinning, with low cost, high energy density, high power performance and high safety performance, reducing battery internal resistance and heat production, and improving processing performance and capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170859A_ABST
    Figure CN119170859A_ABST
Patent Text Reader

Abstract

Provided are a secondary battery (5), and a battery module (4), a battery pack (1), and an electric device including the same. The secondary battery comprises a positive pole piece and a non-aqueous electrolyte, the non-aqueous electrolyte comprises a compound as shown in a formula 1, the non-aqueous electrolyte comprises a first lithium salt, the first lithium salt comprises a combination of lithium hexafluorophosphate and lithium bis (fluorosulfonyl) imide, the mass percentage content of the lithium hexafluorophosphate is A2%, the mass percentage content of the lithium bis (fluorosulfonyl) imide is A3%, and the mass percentage content of the lithium bis (fluorosulfonyl) imide is A3%. A2 is 6 to 14, A3 is greater than 0, and A3 / A2 is 0.8 or less, based on the total mass of the non-aqueous electrolyte solution; the thickness of the positive current collector is H [mu] m, and H is 4-14. The secondary battery adopting the thinned positive electrode current collector has the advantages of low cost, high energy density, high power performance, good processing performance and high safety performance. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

This application is a divisional application based on the invention with application number 202280012717.0, application date May 23, 2022, applicant being Contemporary Amperex Technology Co., Ltd., and invention name being “Secondary batteries and battery modules, battery packs and electrical devices containing the same”. Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a secondary battery and a battery module, a battery pack and an electrical device containing the same. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the application and promotion of secondary batteries, the requirements for their energy density are becoming increasingly higher. Aluminum foil current collectors do not contribute to the capacity of secondary batteries. Thinning the aluminum foil current collector can not only reduce costs but also accommodate more active materials in the limited battery shell. Therefore, thinning the aluminum foil current collector is one of the most effective measures to improve the energy density of secondary batteries. Although thinning the aluminum foil current collector can reduce costs and increase the energy density of secondary batteries, this solution is difficult to apply in practice in industry. This is mainly because after thinning the aluminum foil current collector, the internal resistance of the battery increases, the heat generation increases, and the processing performance of the positive electrode sheet deteriorates, making it prone to breakage. As a result, current secondary batteries cannot simultaneously achieve low cost, high energy density, high power performance, good processing performance, and high safety performance. Summary of the Invention

[0003] The purpose of this application is to provide a secondary battery and a battery module, a battery pack and an electrical device containing the same, aiming to make the secondary battery using a thinned positive electrode current collector have low cost, high energy density, high power performance, good processing performance and high safety performance.

[0004] In a first aspect, the present application provides a secondary battery, comprising a positive electrode plate and a non-aqueous electrolyte, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector, wherein the non-aqueous electrolyte comprises a compound represented by Formula 1, wherein X and Y each independently represent a fluorine atom, or at least one of the group consisting of the following partially fluorinated or fully fluorinated groups: a C1-C10 alkyl group, a C2-C10 alkenyl group, a C2-C10 alkynyl group, a C6-C8 aryl group, a C1-C10 alkoxy group, a C2-C10 alkenyloxy group, a C2-C10 alkynyloxy group, and a C6-C8 aryloxy group, and at least one of X and Y represents a fluorine atom; The non-aqueous electrolyte includes a first lithium salt, which includes a combination of lithium hexafluorophosphate and lithium bisfluorosulfonyl imide. The mass percentage of the lithium hexafluorophosphate is A2%, and the mass percentage of the lithium bisfluorosulfonyl imide is A3%, both based on the total mass of the non-aqueous electrolyte, A2 is 6 to 14, A3 is greater than 0, and A3 / A2 is less than 0.8; the thickness of the positive electrode current collector is H μm, and H is 4 to 14.

[0005] When the non-aqueous electrolyte contains the compound shown in Formula 1, it helps to form a passivation film on the surface of the positive electrode current collector, improving the processing performance of the positive electrode sheet and the secondary battery; it also helps to form a low-impedance interface film on the surface of the positive electrode active material, improving the power performance and safety performance of the secondary battery; it also helps to increase the number of active lithium ions and contribute part of the capacity.

[0006] Lithium hexafluorophosphate has high ionic conductivity. Therefore, when its content is within an appropriate range, it helps improve the overall ionic conductivity of the non-aqueous electrolyte, accelerates lithium ion transport, and enhances the capacity retention of the secondary battery. When the non-aqueous electrolyte contains both the compound represented by Formula 1 and lithium hexafluorophosphate, the compound represented by Formula 1 reacts with the lithium hexafluorophosphate to form the compound LiPF4C2O4, thereby reducing the decomposition of the lithium hexafluorophosphate and the formation of HF, thereby further enhancing the secondary battery's excellent cycling performance.

[0007] Lithium bis(fluorosulfonyl)imide (liSF2) has the chemical formula F2NO4S2.Li. The nitrogen atom is attached to two electron-withdrawing sulfonyl groups, resulting in a fully delocalized charge on the nitrogen atom. This results in a low lattice energy and easy dissociation, which improves the ionic conductivity and reduces the viscosity of non-aqueous electrolytes. Furthermore, lithium bis(fluorosulfonyl)imide exhibits excellent high-temperature resistance and is resistant to hydrolysis, forming a thinner, lower-impedance, and more thermally stable interfacial film on the surface of the anode active material, thereby reducing side reactions between the anode active material and the non-aqueous electrolyte. An A3 / A2 ratio below 0.8 ensures that the non-aqueous electrolyte is less susceptible to hydrolysis and has higher thermal stability, while also contributing to the formation of a lower-impedance interfacial film.

[0008] In any embodiment of the present application, optionally, A3 / A2 is 0.01 to 0.8, more optionally 0.05 to 0.6, thereby facilitating the formation of an interface film with lower impedance.

[0009] In any embodiment of the present application, optionally, A2 is 8 to 12.

[0010] In any embodiment of the present application, optionally, H is 9 to 14.

[0011] In any embodiment of the present application, optionally, A3 is greater than 0 and less than or equal to 5, and can be optionally 0.1 to 2.5.

[0012] In any embodiment of the present application, optionally, the non-aqueous electrolyte further includes a second lithium salt, the second lithium salt including at least one of lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium difluorophosphate, lithium difluorobis(oxaloyl)phosphate, and lithium tetrafluorooxaloylphosphate, and the total mass percentage of the second lithium salt in the non-aqueous electrolyte is A4%, based on the total mass of the non-aqueous electrolyte. Optionally, A4 is less than 5, more preferably less than 2. The second lithium salt can serve as an auxiliary lithium salt to further improve the interfacial properties of the positive electrode and / or negative electrode, or to improve the ionic conductivity or thermal stability of the non-aqueous electrolyte.

[0013] In any embodiment of the present application, optionally, the second lithium salt includes lithium difluorophosphate. Optionally, the mass ratio α of the lithium difluorophosphate to the lithium hexafluorophosphate is 0.01 to 0.15, more optionally 0.01 to 0.1. Lithium difluorophosphate has high electrochemical stability, can improve the ionic conductivity of the non-aqueous electrolyte, improve the properties of the positive electrode interface film and / or the negative electrode interface film, and help to construct a stable and low-impedance positive electrode interface film and / or negative electrode interface film, thereby effectively reducing the decomposition of the non-aqueous electrolyte and further improving the power performance and safety performance of the secondary battery.

[0014] In any embodiment of the present application, optionally, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and A2 / A1 is 5 to 650, more optionally 15 to 300. This helps to further improve the capacity retention rate of the secondary battery while improving the problems of power performance degradation, increased safety hazards, and poor processing performance caused by thinning of the positive electrode current collector.

[0015] In any embodiment of the present application, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and A1 is 0.02 to 1.8, optionally 0.02 to 0.5. This can improve the defects such as poor power performance, increased safety hazards, and poor processing performance caused by thinning the positive electrode current collector.

[0016] In any embodiment of the present application, optionally, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and A1 / H is 0.0015 to 0.20, optionally 0.002 to 0.05, and more optionally 0.01 to 0.05. This helps to increase the strength of the positive electrode current collector, improve the processing performance of the positive electrode sheet, reduce or even avoid the occurrence of belt breakage, and also helps the secondary battery have high power performance and high safety performance.

[0017] In any embodiment of the present application, optionally, the compaction density of the positive electrode active material layer is P g / cm 3 , P is 3.2 to 3.7, more preferably 3.4 to 3.7. This helps to improve the energy density of the secondary battery.

[0018] In any embodiment of the present application, optionally, the compaction density of the positive electrode active material layer is P g / cm 3 Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and P / A1 is 2 to 340, optionally 5 to 100. This helps to improve the power performance and safety performance of the secondary battery.

[0019] In any embodiment of the present application, the positive electrode current collector may optionally have an elongation at break of Q%, wherein Q is 0.5 to 3.5, more preferably 1.5 to 3.5. This allows the positive electrode current collector to have high strength and good processing properties, is not prone to breakage, and contributes to high safety performance of the secondary battery.

[0020] In any embodiment of the present application, the elongation at break of the positive electrode current collector is optionally Q%, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and Q + A1 is 1 to 4, optionally 1.5 to 3.5, and more optionally 2.0 to 3.5. This helps to increase the strength of the positive electrode current collector, improve the processing performance of the positive electrode sheet, reduce or even avoid the occurrence of band breakage, and also helps the secondary battery have high power performance and high safety performance.

[0021] In any embodiment of the present application, the compaction density of the positive electrode active material layer is P g / cm 3 The positive electrode current collector has an elongation at break of Q%, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and the secondary battery satisfies the following conditions: H is 11 to 14, A1 / H is 0.005 to 0.15, Q+A1 is 1 to 4, and P / A1 is 2 to 100. Optionally, A1 / H is 0.005 to 0.1, Q+A1 is 1.5 to 3.5, and P / A1 is 5 to 75.

[0022] In any embodiment of the present application, the compaction density of the positive electrode active material layer is P g / cm 3, the elongation at break of the positive electrode current collector is Q%, the mass percentage of the compound represented by Formula 1 is A1%, based on the total mass of the non-aqueous electrolyte, and the secondary battery satisfies the following conditions: H is 4 to 11, A1 / H is 0.006 to 0.1, Q+A1 is 1 to 4, and P / A1 is 2 to 100. Optionally, H is 9 to 11, A1 / H is 0.01 to 0.05, Q+A1 is 1.5 to 3.5, and P / A1 is 5 to 75.

[0023] In any embodiment of the present application, the non-aqueous electrolyte further comprises a cyclic carbonate compound, wherein the mass percentage of the cyclic carbonate compound is B1%, based on the total mass of the non-aqueous electrolyte. Optionally, B1 is 0.5 to 20, more preferably 15 to 18.

[0024] In any embodiment of the present application, the non-aqueous electrolyte further comprises a cyclic carbonate compound, the mass percentage of the cyclic carbonate compound is B1%, and the mass percentage of the compound represented by Formula 1 is A1%, both based on the total mass of the non-aqueous electrolyte. Optionally, B1 / 20+A1 is 1 to 3, more optionally 1 to 2. This helps to further improve the capacity retention of the secondary battery while improving the problems of poor power performance, increased safety hazards, and poor processing performance caused by thinning of the positive electrode current collector.

[0025] In any embodiment of the present application, optionally, the cyclic carbonate compound includes at least one of ethylene carbonate, propylene carbonate, vinylene carbonate, and vinylethylene carbonate.

[0026] In any embodiment of the present application, optionally, the non-aqueous electrolyte further comprises a chain carbonate compound, and the mass percentage of the chain carbonate compound is B2%, where B2 is 45 to 80, based on the total mass of the non-aqueous electrolyte.

[0027] In any embodiment of the present application, optionally, the non-aqueous electrolyte further comprises a carboxylate compound, and the mass percentage of the carboxylate compound is B3%, where B3 is 2 to 15.

[0028] In any embodiment of the present application, optionally, the non-aqueous electrolyte further includes additives, and the additives include at least one of halogen-substituted cyclic carbonate compounds, nitrile compounds, phosphazene compounds, aromatic hydrocarbons and halogenated aromatic hydrocarbon compounds, isocyanate compounds, acid anhydride compounds, sulfate compounds, sulfite compounds, sulfonate compounds, and disulfonate compounds, and the total mass percentage of the additives is less than 5%, based on the total mass of the non-aqueous electrolyte.

[0029] In any embodiment of the present application, the non-aqueous electrolyte may further comprise fluoroethylene carbonate, with a mass percentage of C1% based on the total mass of the non-aqueous electrolyte. Alternatively, 0 < C1 ≤ 2.5, and more preferably, 0 < C1 ≤ 2.0. This can effectively improve the cycling performance of the secondary battery.

[0030] In any embodiment of the present application, optionally, the non-aqueous electrolyte further comprises fluoroethylene carbonate, whose mass percentage is C1%, and the mass percentage of the compound represented by Formula 1 is A1%, both based on the total mass of the non-aqueous electrolyte, 0.25≤C1 / A1≤25, more optionally, 0.5≤C1 / A1≤10. This helps to further improve the cycle performance of the secondary battery while improving the problems of power performance degradation, increased safety hazards, and poor processing performance caused by thinning of the positive electrode current collector.

[0031] In any embodiment of the present application, optionally, the non-aqueous electrolyte further includes a dewatering additive, and the dewatering additive includes at least one of hexamethyldisilazane and tris(trimethylsilyl)phosphate. Optionally, the mass percentage of the dewatering additive is less than 2%, more optionally 0.05% to 1%, based on the total mass of the non-aqueous electrolyte. This helps to further improve the power performance, storage performance and safety performance of the secondary battery.

[0032] In any embodiment of the present application, optionally, X and Y both represent fluorine atoms.

[0033] In any embodiment of the present application, optionally, one of X and Y represents a fluorine atom, and the other represents at least one of the group consisting of the following partially fluorinated or fully fluorinated groups: C1-C5 alkyl, C2-C5 alkenyl, C2-C5 alkynyl, phenyl, phenoxy, C1-C5 alkoxy, C2-C5 alkenyloxy and C2-C5 alkynyloxy.

[0034] In any embodiment of the present application, optionally, one of X and Y represents a fluorine atom, and the other represents at least one of the group consisting of the following partially fluorinated or fully fluorinated groups: methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, vinyl, propenyl, allyl, butadienyl, ethynyl, propynyl, phenyl, methoxy, ethoxy, propoxy, vinyloxy, propenyloxy, ethynyloxy, propynyloxy and phenoxy.

[0035] The presence of fluorine atoms helps to form a thinner fluorine-containing positive electrode interface film and / or negative electrode interface film, thereby facilitating the uniform transport of lithium ions and effectively inhibiting the formation of lithium dendrites.

[0036] In any embodiment of the present application, optionally, the compound represented by Formula 1 includes at least one of the following compounds:

[0037] In any embodiment of the present application, optionally, the positive electrode current collector is made of aluminum foil or aluminum alloy foil.

[0038] In any embodiment of the present application, optionally, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a lithium transition metal oxide, an olivine-structured lithium-containing phosphate, and modified compounds thereof.

[0039] A second aspect of the present application provides a battery module, which includes the secondary battery according to the first aspect of the present application.

[0040] A third aspect of the present application provides a battery pack, which includes the secondary battery of the first aspect of the present application and the battery module of the second aspect.

[0041] A fourth aspect of the present application provides an electrical device comprising at least one of the secondary battery of the first aspect of the present application, the battery module of the second aspect, and the battery pack of the third aspect.

[0042] The battery module, battery pack and electric device of the present application include the secondary battery provided by the present application, and thus have at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0044] Figure 1 This is a schematic diagram of one embodiment of the secondary battery of the present application.

[0045] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a secondary battery.

[0046] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0047] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0048] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0049] Figure 6 This is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source.

[0050] In the accompanying drawings, which are not necessarily drawn to scale, reference numerals are as follows: 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0051] Below, the embodiments of the secondary battery of the present application and the battery module, battery pack and electrical device containing the same are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0052] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.

[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.

[0055] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0057] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0058] Throughout this specification, substituents of compounds are disclosed in groups or ranges. It is expressly intended that such descriptions include each individual subcombination of the members of these groups and ranges. For example, it is expressly intended that the term "C1-C6 alkyl" individually discloses C1, C2, C3, C4, C5, C6, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C6, C2-C5, C2-C4, C2-C3, C3-C6, C3-C5, C3-C4, C4-C6, C4-C5, and C5-C6 alkyl.

[0059] In this application, the terms "plurality" and "multiple" refer to two or more.

[0060] In this application, the thickness of the current collector and the active material layer has a well-known meaning in the art and can be measured using methods known in the art, such as using a micrometer.

[0061] In the present application, the compacted density of the active material layer has a meaning well known in the art and can be tested by methods known in the art. The compacted density of the active material layer = the surface density of the active material layer / the thickness of the active material layer. The surface density of the active material layer has a meaning well known in the art and can be tested by methods known in the art, for example, take an electrode sheet that is coated on one side and cold pressed (if it is an electrode sheet coated on both sides, the active material layer on one side can be wiped off first), punch it into small discs with an area of ​​S0, weigh it, and record it as M1; then wipe off the active material layer of the weighed electrode sheet, weigh the weight of the current collector, and record it as M0. The surface density of the active material layer = (M1-M0) / S0.

[0062] In the present application, the elongation at break of the positive electrode current collector refers to the elongation at break at room temperature.

[0063] Aluminum foil current collector is one of the essential components of secondary batteries, and in order to further improve the energy density of secondary batteries, thinning the aluminum foil current collector is still one of the most effective measures. Although thinning the aluminum foil current collector can reduce costs and increase the energy density of secondary batteries, this solution is difficult to apply in practice in industry. The main reasons include the following: First, after the aluminum foil current collector is thinned, the resistance of the aluminum foil increases, which leads to an increase in the internal resistance of the battery and poor power performance; second, since aluminum foil is a good thermal conductor material, its thinning will lead to an increase in the heat generation of the secondary battery and difficulty in heat dissipation, thereby increasing the safety risks of the secondary battery; third, after the aluminum foil current collector is thinned, its own strength deteriorates. At the same time, in order to further improve the energy density of the secondary battery, the thinned aluminum foil current collector is usually used with a higher compaction density. As a result, the positive electrode sheet is easily broken during the rolling process, affecting the processing performance of the positive electrode sheet and the secondary battery.

[0064] Furthermore, high-power batteries require a high discharge current during use, generating high heat during discharge. At high temperatures, the decomposition reaction of the non-aqueous electrolyte at the positive and negative electrode interfaces increases significantly, causing a significant increase in the positive and negative electrode interface impedances, leading to a decrease in the power performance of the secondary battery. Currently, thickening the aluminum foil current collector is a common approach to achieving high-power batteries.

[0065] Therefore, the current solution of increasing the energy density of secondary batteries by thinning the positive electrode current collector still faces many difficulties in practical applications, such as deterioration of power performance, increased safety hazards, and deterioration of processing performance.

[0066] The inventors of this application were pleasantly surprised to find during the research process that by adopting a suitable non-aqueous electrolyte, they can solve the problems of deteriorating power performance, increased safety hazards, and deteriorating processing performance caused by thinning of the positive electrode current collector, thereby enabling the secondary battery to simultaneously take into account low cost, high energy density, high power performance, good processing performance and high safety performance.

[0067] Specifically, an embodiment of the present application provides a secondary battery.

[0068] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can be recharged to activate active materials and continue to be used after the battery is discharged. The secondary battery of the present application may be a lithium secondary battery, in particular, a lithium-ion secondary battery. The secondary battery includes an electrode assembly, a non-aqueous electrolyte, and an outer packaging, and the outer packaging is used to encapsulate the electrode assembly and the non-aqueous electrolyte. The electrode assembly generally includes a positive electrode sheet, and the electrode assembly may also include a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing lithium ions to pass through. In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be made into an electrode assembly by a winding process or a lamination process.

[0069] The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in the thickness direction, and the positive electrode active material layer is provided on any one or both of the two opposite surfaces of the positive electrode current collector. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in the thickness direction, and the negative electrode active material layer is provided on any one or both of the two opposite surfaces of the negative electrode current collector. During the charge and discharge process of the secondary battery, lithium ions are embedded and extracted back and forth between the positive electrode plate and the negative electrode plate. The non-aqueous electrolyte includes a lithium salt and an organic solvent, which is used to conduct lithium ions between the positive electrode plate and the negative electrode plate.

[0070] In the secondary battery of the present application, the non-aqueous electrolyte includes the compound represented by Formula 1, X and Y each independently represent a fluorine atom, or at least one of the group consisting of the following groups which are partially fluorinated or fully fluorinated: a C1-C10 alkyl group, a C2-C10 alkenyl group, a C2-C10 alkynyl group, a C6-C8 aryl group, a C1-C10 alkoxy group, a C2-C10 alkenyloxy group, a C2-C10 alkynyloxy group, a C6-C8 aryloxy group, and at least one of X and Y represents a fluorine atom.

[0071] Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, the thickness of the positive electrode current collector is H μm, the elongation at break of the positive electrode current collector is Q%, and the compaction density of the positive electrode active material layer is P g / cm 3, and the secondary battery satisfies: H is 4 to 14, A1 / H is 0.0015 to 0.20, Q+A1 is 1 to 4, and P / A1 is 2 to 340.

[0072] In the present application, the thickness H μm of the positive electrode current collector satisfies that H is between 4 and 14. Optionally, H may be between 4 and 13, between 4 and 12, between 4 and 11, between 4 and 10, between 4 and 9, or between 4 and 8.

[0073] The inventors of the present application have found in the course of their research that in a secondary battery using a thinned positive electrode current collector, when the non-aqueous electrolyte contains the compound represented by Formula 1 and by controlling its content A1% and the thickness Hμm of the positive electrode current collector, the elongation at break Q% of the positive electrode current collector and the compaction density P g / cm 3 When the relationship between the two is such that the secondary battery satisfies A1 / H of 0.0015 to 0.20, Q+A1 of 1 to 4 and P / A1 of 2 to 340, the secondary battery can simultaneously take into account low cost, high energy density, high power performance, good processing performance and high safety performance.

[0074] Although the mechanism is still unclear, the inventors speculate that the possible reasons include the following.

[0075] First, the molecular structure of the compound represented by Formula 1 contains an oxalate group, which can be oxidized on the surface of the positive electrode active material in preference to the organic solvent, and its oxidation product also has a low impedance characteristic, thereby contributing to the formation of a low-impedance positive electrode interface film; at the same time, the B atom in the molecular structure of the compound represented by Formula 1 is also easy to firmly combine with inorganic components such as LiF in the positive electrode interface film, thereby accelerating lithium ion transmission and significantly reducing the internal resistance of the battery, so that the secondary battery has high energy density while also having high power performance and capable of large current discharge.

[0076] Second, the BO bond energy in the molecular structure of the compound shown in formula 1 is 3+ Bonding and forming a passivation film on the surface of the positive electrode current collector, thereby helping to improve the strength of the positive electrode current collector, improve the processing performance of the positive electrode sheet, reduce or even avoid the occurrence of broken belts, and make the practical application of thinning the positive electrode current collector possible. The molecular structure of the compound shown in Formula 1 contains fluorine atoms, which can react with Al 3+ Bonding can improve the strength of the positive electrode sheet, improve the processing performance of the positive electrode sheet, reduce or even avoid the occurrence of broken strips, and make the practical application of thinning the positive electrode current collector possible.

[0077] Third, the compound shown in Formula 1 has a high thermal stability, for example, it is worse than the common LiPF6, which helps to improve the overall heat resistance of the non-aqueous electrolyte; at the same time, the compound shown in Formula 1 is not as sensitive to water as LiPF6, which also helps to improve the water resistance of the non-aqueous electrolyte, reduce HF formation and reduce the acidity of the non-aqueous electrolyte. Therefore, the non-aqueous electrolyte of the present application can have high thermal stability and electrochemical stability, thereby reducing the decomposition of the non-aqueous electrolyte at high temperatures and reducing the internal resistance of the battery. According to Joule's law, the heat generation of the secondary battery is directly related to the internal resistance of the battery. Therefore, when the internal resistance of the battery is reduced, the heat generation of the secondary battery is also reduced, which enables the secondary battery to have high power performance and high safety performance while having high energy density.

[0078] Fourth, the inventors were also surprised to find that since the anion portion of the compound represented by Formula 1 is easily oxidized, the lithium ions dissociated from its molecular structure can also become active lithium ions, contributing part of the capacity, thereby helping to further improve the energy density of the secondary battery.

[0079] Therefore, when the non-aqueous electrolyte contains the compound shown in Formula 1, it helps to form a passivation film on the surface of the positive electrode current collector, improving the processing performance of the positive electrode sheet and the secondary battery; it also helps to form a low-impedance interface film on the surface of the positive electrode active material, improving the power performance and safety performance of the secondary battery; it also helps to increase the number of active lithium ions and contribute part of the capacity. However, the inventors of this application found in further research that the content of the compound shown in Formula 1 also needs to be reasonably matched with the thickness of the positive electrode current collector, the elongation at break of the positive electrode current collector, and the compaction density of the positive electrode active material layer to reduce the negative impact of the thinning of the positive electrode current collector on the power performance, processing performance, and safety performance, so that the secondary battery can simultaneously take into account low cost, high energy density, high power performance, good processing performance, and high safety performance.

[0080] In the present application, the content A1% of the compound shown in Formula 1 and the thickness Hμm of the positive electrode current collector satisfy A1 / H between 0.0015 and 0.20. Therefore, the BO bond energy in the molecular structure of the compound shown in Formula 1 is 3+ Better bonding and forming a passivation film with a suitable thickness on the surface of the positive current collector, thereby helping to improve the strength of the positive current collector, improve the processing performance of the positive electrode sheet, and reduce or even avoid the occurrence of broken belts. When A1 / H is less than 0.0015, the positive current collector is thicker and the content of the compound shown in Formula 1 is low, and there is not enough compound shown in Formula 1 to react with Al 3+Bonding and forming a passivation film on the surface of the positive electrode collector, resulting in poor processing performance of the positive electrode sheet and the secondary battery; when A1 / H is greater than 0.20, the positive electrode collector is thin and the content of the compound represented by Formula 1 is high, resulting in the formation of an excessively thick interface film, thereby increasing the positive electrode interface impedance and / or the negative electrode interface impedance, and thus increasing the battery internal resistance and heat generation, and deteriorating the power performance and safety performance of the secondary battery. Optionally, A1 / H is 0.002 to 0.15, 0.002 to 0.1, 0.002 to 0.08, 0.002 to 0.07, 0.002 to 0.06, 0.002 to 0.05, 0.005 to 0.15, 0.005 to 0.1, 0.005 to 0.08, 0.005 to 0.07, 0.005 to 0.06, 0.005 to 0.05, 0.01 to 0.15, 0.01 to 0.1, 0.01 to 0.08, 0.01 to 0.07, 0.01 to 0.06 or 0.01 to 0.05.

[0081] In the present application, the content A1% of the compound shown in Formula 1 and the elongation at break Q% of the positive electrode current collector satisfy Q+A1 between 1 and 4. Thus, the BO bond energy in the molecular structure of the compound shown in Formula 1 is substantially equal to that of Al 3+ Better bonding and forming a passivation film with a suitable thickness on the surface of the positive current collector, thereby helping to improve the strength of the positive current collector, improve the processing performance of the positive electrode sheet, and reduce or even avoid the occurrence of broken belts. When Q+A1 is less than 1, there is not enough compound represented by formula 1 to react with Al 3+ Bonding and forming a passivation film on the surface of the positive electrode collector, at the same time, the ductility of the positive electrode collector is poor, and the belt is easily broken during the rolling process, resulting in poor processing performance of the positive electrode sheet and the secondary battery; when Q+A1 is greater than 4, the positive electrode collector has high ductility and good pressure resistance, but it is not puncture-resistant. When squeezed by sharp substances (such as hard carbon particles that are usually sharp in shape), it is easy to be damaged and large burrs will appear, causing a high risk of short circuit in the battery. Therefore, the safety performance of the secondary battery cannot be effectively improved. At the same time, more compounds represented by Formula 1 will also lead to the formation of an excessively thick interface film, thereby the positive electrode interface impedance and / or the negative electrode interface impedance will be high, and the power performance and safety performance of the secondary battery are poor. Optionally, Q+A1 is 1.5 to 4, 1.8 to 4, 2.0 to 4, 2.2 to 4, 2.4 to 4, 2.6 to 4, 2.8 to 4, 3.0 to 4, 1.5 to 3.5, 1.8 to 3.5, 2.0 to 3.5, 2.2 to 3.5, 2.4 to 3.5, 2.6 to 3.5, 2.8 to 3.5 or 3.0 to 3.5.

[0082] In this application, the content of the compound represented by Formula 1 is A1% and the compaction density of the positive electrode active material layer is P g / cm 3P / A1 is satisfied to be between 2 and 340. Thus, the compound represented by Formula 1 helps to form a low-impedance interface film on the surface of the positive electrode active material, thereby reducing the positive electrode interface impedance. At the same time, it also helps the B atoms in the molecular structure of the compound represented by Formula 1 to better combine with the O atoms in the positive electrode active material, thereby reducing the charge transfer impedance and lithium ion bulk diffusion resistance of the positive electrode active material, thereby reducing the internal resistance and heat generation of the battery and improving the power performance and safety performance of the secondary battery. When P / A1 is less than 2, the compaction density of the positive electrode active material layer is small and the content of the compound represented by Formula 1 is high, resulting in the formation of an excessively thick interface film, thereby increasing the positive electrode interface impedance and / or the negative electrode interface impedance, and thus the battery internal resistance and heat generation are high, and the power performance and safety performance of the secondary battery are poor; when P / A1 is greater than 340, the compaction density of the positive electrode active material layer is large and the content of the compound represented by Formula 1 is low, there is not enough compound represented by Formula 1 to form a low-impedance interface film on the surface of the positive electrode active material, and the charge transfer impedance and lithium ion bulk diffusion resistance of the positive electrode active material are high, thereby increasing the battery internal resistance and heat generation, and the power performance and safety performance of the secondary battery are poor. Alternatively, P / A1 is 2 to 200, 2 to 100, 2 to 75, 2 to 50, 2 to 35, 2 to 30, 2 to 25, 2 to 20, 2 to 15, 3.5 to 340, 3.5 to 200, 3.5 to 100, 3.5 to 75, 3.5 to 50, 3.5 to 35, 3.5 to 30, 3.5 to 25, 3.5 to 20, 3.5 to 15, 5 to 340, 5 to 200, 5 to 100, 5 to 75, 5 to 50, 5 to 35, 5 to 30, 5 to 25, 5 to 20, 10 to 340, 10 to 200, 10 to 100, 10 to 75, 10 to 50, 10 to 35, 10 to 30, 10 to 25 or 10 to 20.

[0083] In some embodiments, optionally, the secondary battery satisfies: H is 4 to 14, A1 / H is 0.01 to 0.05, Q+A1 is 1.5 to 3.5, and P / A1 is 10 to 340. More optionally, the secondary battery satisfies: H is 4 to 14, A1 / H is 0.01 to 0.05, Q+A1 is 2.0 to 3.5, and P / A1 is 10 to 340.

[0084] In the present application, at least one of X and Y represents a fluorine atom. The presence of a fluorine atom helps to form a thinner fluorine-containing positive electrode interface film and / or negative electrode interface film, thereby facilitating the uniform transmission of lithium ions and effectively inhibiting the formation of lithium dendrites. In some embodiments, one of X and Y represents a fluorine atom, and the other represents at least one of the following groups consisting of partially fluorinated or fully fluorinated groups: C1-C5 alkyl, C2-C5 alkenyl, C2-C5 alkynyl, phenyl, phenoxy, C1-C5 alkoxy, C2-C5 alkenyloxy and C2-C5 alkynyloxy. Alternatively, one of X and Y represents a fluorine atom, and the other represents at least one of the following groups consisting of partially fluorinated or fully fluorinated groups: methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, vinyl, propenyl, allyl, butadienyl, ethynyl, propynyl, phenyl, methoxy, ethoxy, propoxy, vinyloxy, propenyloxy, ethynyloxy, propynyloxy and phenoxy.

[0085] In some embodiments, X and Y both represent fluorine atoms.

[0086] As an example, the compound represented by Formula 1 includes at least one of the following compounds:

[0087] In some embodiments, the positive electrode current collector is made of aluminum foil or aluminum alloy foil. To improve the corrosion resistance and strength of the positive electrode current collector, aluminum foil with a purity of 99.99% or greater is optionally used. The aluminum alloy foil, in addition to aluminum, also contains at least one of iron, magnesium, zinc, manganese, and silicon. For example, the aluminum alloy foil may be an Al-Fe alloy foil, an Al-Mn alloy foil, or an Al-Mg alloy foil. The aluminum alloy foil may optionally have an aluminum content of 95% to 99.5% by weight, more preferably 98% to 99.5% by weight.

[0088] In some embodiments, A1 is 0.02 to 1.8. Alternatively, A1 is 0.02 to 1.6, 0.02 to 1.4, 0.02 to 1.2, 0.02 to 1.0, 0.02 to 0.8, 0.02 to 0.7, 0.02 to 0.6, 0.02 to 0.5, 0.05 to 1.6, 0.05 to 1.4, 0.05 to 1.2, 0.05 to 1.0, 0.05 to 0.8, 0.05 to 0.7, 0.05 to 0.6, 0.05 to 0.5, 0.1 to 1.6, 0.1 to 1.4, 0.1 to 1.2, 0.1 to 1.0, 0.1 to 0.8, 0.1 to 0.7, 0.1 to 0.6 or 0.1 to 0.5. When the content of the compound represented by Formula 1 is within an appropriate range, a passivation film with an appropriate thickness can be formed on the surface of the positive electrode current collector, and a low-impedance interface film can be formed on the surface of the positive electrode active material, thereby improving the defects such as poor power performance, increased safety hazards, and poor processing performance caused by the thinning of the positive electrode current collector. It can also effectively avoid the following situation: when the content of the compound represented by Formula 1 is low, there is not enough compound represented by Formula 1 to react with Al 3+ Bonding and forming a passivation film on the surface of the positive electrode current collector, thereby poor processing performance of the positive electrode sheet and the secondary battery; when the content of the compound represented by Formula 1 is high, the positive electrode interface impedance and / or the negative electrode interface impedance increase, the battery internal resistance and heat generation increase, and the power performance and safety performance of the secondary battery deteriorate.

[0089] In some embodiments, Q is 0.5 to 3.5. Optionally, Q is 1 to 3.5, 1.5 to 3.5, 1.8 to 3.5, 2.0 to 3.5, 2.2 to 3.5, 2.4 to 3.5, 2.6 to 3.5, 2.8 to 3.5 or 3.0 to 3.5. When the elongation at break of the positive electrode collector is within an appropriate range, the positive electrode collector has high strength and good processing performance, and is not prone to breaking. It can also effectively avoid the following situations: when the elongation at break of the positive electrode collector is small, the ductility of the positive electrode collector is poor, and the belt is prone to breaking during the rolling process, resulting in poor processing performance of the positive electrode sheet and the secondary battery; when the elongation at break of the positive electrode collector is large, it is not puncture-resistant, and is easily damaged and has large burrs when squeezed by sharp objects, causing a high risk of short circuit in the battery, and thus the safety performance of the secondary battery is still not effectively improved.

[0090] In some embodiments, P is 3.2 to 3.7. Alternatively, P is 3.3 to 3.7, 3.4 to 3.7, 3.5 to 3.7, 3.2 to 3.6, 3.3 to 3.6, 3.4 to 3.6, or 3.5 to 3.6. When the compaction density of the positive electrode active material layer is in a higher range, it helps to improve the energy density of the secondary battery.

[0091] In some embodiments, when the thickness H μm of the positive electrode current collector satisfies H being greater than 11 and less than 14, specifically, H being 11 to 14, optionally 12 to 14, or 12 to 13, the secondary battery satisfies: A1 / H being 0.005 to 0.15, Q+A1 being 1 to 4, and P / A1 being 2 to 100. Optionally, the secondary battery satisfies: A1 / H being 0.005 to 0.1, Q+A1 being 1.5 to 3.5, and P / A1 being 5 to 75.

[0092] In some embodiments, when the thickness H μm of the positive electrode current collector satisfies H being greater than 4 and less than 11, optionally less than 10, less than 9, or less than 8, specifically, H being 4 to 11, optionally 4 to 10, 4 to 9, or 4 to 8, the secondary battery satisfies: A1 / H being 0.006 to 0.1, Q+A1 being 1 to 4, and P / A1 being 2 to 100. Optionally, A1 / H being 0.01 to 0.05, Q+A1 being 1.5 to 3.5, and P / A1 being 5 to 75. [Lithium salt]

[0093] In some embodiments, the non-aqueous electrolyte includes a first lithium salt, which is lithium hexafluorophosphate (LiPF6) or a combination of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI). Lithium hexafluorophosphate has the characteristic of high ionic conductivity, so when its content is within a suitable range, it helps to improve the overall ionic conductivity of the non-aqueous electrolyte, accelerate lithium ion transmission, and improve the capacity retention rate of the secondary battery. However, lithium hexafluorophosphate has poor thermal stability in high temperature environments and will decompose to form PF5 at higher temperatures. PF5 reacts with water to form HF, which easily corrodes the positive electrode active material and increases battery flatulence. When the non-aqueous electrolyte contains both the compound represented by Formula 1 and lithium hexafluorophosphate, the compound represented by Formula 1 can react with lithium hexafluorophosphate to form the compound LiPF4C2O4, thereby reducing the decomposition of some lithium hexafluorophosphate and the formation of HF, and thus the secondary battery can also have good cycle performance. The chemical formula of lithium bis(fluorosulfonyl)imide is F2NO4S2. The Li and N atoms are linked to two electron-withdrawing sulfonyl groups, which fully delocalizes the charge on the N atoms. Consequently, lithium bis(fluorosulfonyl)imide has a low lattice energy and is easily dissociated, thereby improving the ionic conductivity and reducing the viscosity of the non-aqueous electrolyte. Furthermore, lithium bis(fluorosulfonyl)imide exhibits excellent high-temperature resistance and is not easily hydrolyzed, forming a thinner, lower-impedance, and more thermally stable interfacial film on the surface of the negative electrode active material, thereby reducing side reactions between the negative electrode active material and the non-aqueous electrolyte. However, lithium bis(fluorosulfonyl)imide is prone to corroding the positive electrode current collector, so its content should not be too high.

[0094] In some embodiments, optionally, the mass percentage of the lithium hexafluorophosphate is A2%, and A2 is 6 to 14, based on the total mass of the non-aqueous electrolyte. More optionally, A2 is 6 to 12, 6 to 10, 8 to 14, 8 to 12, or 8 to 10.

[0095] In some embodiments, optionally, the mass percentage of the lithium bis(fluorosulfonyl)imide is A3%, where A3 is greater than 0 and less than or equal to 5, based on the total mass of the non-aqueous electrolyte. More optionally, A3 is 0.1 to 2.5, 0.1 to 2, 0.1 to 1.5, 0.1 to 1, 0.2 to 2.5, 0.2 to 2, 0.2 to 1.5, 0.2 to 1, 0.5 to 2.5, 0.5 to 2, 0.5 to 1.5, or 0.5 to 1.

[0096] In some embodiments, A3 / A2 is optionally below 0.8, more optionally 0.01 to 0.8, 0.05 to 0.8, 0.1 to 0.8, 0.01 to 0.6, 0.05 to 0.6, 0.1 to 0.6, 0.01 to 0.4, 0.05 to 0.4, 0.1 to 0.4, 0.01 to 0.3, 0.05 to 0.3, or 0.1 to 0.3. Thus, the non-aqueous electrolyte is not easily hydrolyzed, and can also have higher thermal stability, while helping to form an interfacial film with lower impedance.

[0097] In some embodiments, A2 / A1 is 5 to 650, based on the total mass of the non-aqueous electrolyte. Lithium hexafluorophosphate has high ionic conductivity. Properly combining the content A1% of the compound represented by Formula 1 with the content A2% of the lithium hexafluorophosphate can help further improve the capacity retention of the secondary battery while addressing issues such as reduced power performance, increased safety hazards, and poor processing performance associated with thinning the positive electrode current collector. And it can effectively avoid the following situations: when the content of lithium hexafluorophosphate is high and the content of the compound represented by formula 1 is low, there may be more PF5 in the non-aqueous electrolyte, which leads to more decomposition reactions of the non-aqueous electrolyte. At the same time, the interface film formed by the compound represented by formula 1 on the positive electrode is not uniform and dense enough, and cannot prevent HF from corroding the positive electrode active material and a series of side reactions caused by it, thereby causing the secondary battery to produce high gas and heat, and the power performance, storage performance and safety performance may deteriorate; when the content of lithium hexafluorophosphate is low and the content of the compound represented by formula 1 is high, since the compound represented by formula 1 is not easy to completely dissociate in the non-aqueous electrolyte, and anions and cations are easy to associate, the ionic conductivity of the non-aqueous electrolyte decreases, and the capacity retention rate of the secondary battery may deteriorate. Alternatively, A2 / A1 is 5 to 500, 5 to 300, 5 to 250, 5 to 200, 5 to 150, 5 to 100, 5 to 75, 5 to 50, 10 to 500, 10 to 300, 10 to 250, 10 to 200, 10 to 150, 10 to 100, 10 to 75, 10 to 50, 15 to 500, 15 to 300, 15 to 250, 15 to 200, 15 to 150, 15 to 100, 15 to 75 or 15 to 50.

[0098] In some embodiments, the non-aqueous electrolyte may further include a second lithium salt, comprising at least one of lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The second lithium salt may serve as an auxiliary lithium salt to further improve the interfacial properties of the positive and / or negative electrodes, or to improve the ionic conductivity or thermal stability of the non-aqueous electrolyte.

[0099] Optionally, the total mass percentage of the second lithium salt in the non-aqueous electrolyte is A4%, where A4 is less than 5, more preferably less than 2, based on the total mass of the non-aqueous electrolyte.

[0100] Optionally, in some embodiments, the second lithium salt includes lithium difluorophosphate (LiPO2F2), lithium tetrafluorooxalophosphate (LiTFOP) or a combination thereof, more optionally, the second lithium salt includes lithium difluorophosphate (LiPO2F2). Lithium difluorophosphate has high electrochemical stability, can improve the ionic conductivity of the non-aqueous electrolyte, improve the properties of the positive electrode interface film and / or the negative electrode interface film, and help to construct a stable and low-impedance positive electrode interface film and / or negative electrode interface film, thereby effectively reducing the decomposition of the non-aqueous electrolyte and further improving the power performance and safety performance of the secondary battery. Optionally, the mass ratio α of lithium difluorophosphate to lithium hexafluorophosphate is 0.01 to 0.15, more optionally 0.01 to 0.1.

[0101] In some embodiments, optionally, A1+A2+A3+A4 is 10 to 20, more optionally 12 to 16. [Organic solvents]

[0102] In some embodiments, the non-aqueous electrolyte includes an organic solvent, and the organic solvent includes at least one of a cyclic carbonate compound, a chain carbonate compound, and a carboxylate compound. Alternatively, the cyclic carbonate compound may include at least one of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), and vinyl ethylene carbonate (VEC). Alternatively, the chain carbonate compound may include at least one of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC). Alternatively, the carboxylate compound may include at least one of methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), and ethyl butyrate (EB).

[0103] Optionally, in some embodiments, the organic solvent includes at least a cyclic carbonate compound and a chain carbonate compound. When the content of lithium salts such as lithium hexafluorophosphate is high, the viscosity of the non-aqueous electrolyte increases and the ionic conductivity decreases, which is not conducive to the transmission of lithium ions. The cyclic carbonate compound can increase the ionic conductivity of the non-aqueous electrolyte due to its higher dielectric constant, and the chain carbonate compound can reduce the viscosity of the non-aqueous electrolyte due to its lower viscosity. Therefore, when the organic solvent includes both a cyclic carbonate compound and a chain carbonate compound, it helps to make the non-aqueous electrolyte have a suitable viscosity and ionic conductivity, which is conducive to the transmission of lithium ions.

[0104] The cyclic carbonate compound has a high dielectric constant, which helps to increase the ionic conductivity of the non-aqueous electrolyte, but is prone to decomposition reactions, affecting the storage performance of the secondary battery. Therefore, its content needs to be controlled within an appropriate range. In some embodiments, the mass percentage of the cyclic carbonate compound is B1%, B1 is greater than 0 and less than or equal to 20, based on the total mass of the non-aqueous electrolyte. Optionally, B1 is 0.5 to 20, 1 to 20, 2 to 20, 5 to 20, 10 to 20, 12 to 20, 15 to 20 or 15 to 18.

[0105] In some embodiments, the mass percentage of the linear carbonate compound is B2%, and B2 is 45 to 80, based on the total mass of the non-aqueous electrolyte. Alternatively, B2 is 50 to 80, 55 to 80, 60 to 80, or 60 to 75.

[0106] Carboxylate compounds have the advantages of low viscosity and high dielectric constant. When applied to non-aqueous electrolytes, they help the non-aqueous electrolytes to have suitable viscosity and ionic conductivity, which is beneficial to the transmission of lithium ions and improves the rate performance of secondary batteries. Carboxylate compounds can improve the power performance of secondary batteries, but their oxidation resistance is poor and they are prone to decomposition when stored in a high state of charge, so their content should not be too high. In some embodiments, the mass percentage of the carboxylate compound is B3%, and B3 is 0 to 15, based on the total mass of the non-aqueous electrolyte. In some embodiments, B3 can be 0. In some embodiments, optionally, B3 is 2 to 15, 2 to 10, 2 to 8 or 2 to 5.

[0107] The organic solvent of the present application may also include other solvents other than the above-mentioned cyclic carbonate compounds, linear carbonate compounds, and carboxylate compounds. As an example, the other solvents may include sulfone solvents such as sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0108] In some embodiments, the content A1% of the compound represented by Formula 1 and the content B1% of the cyclic carbonate compound satisfy B1 / 20+A1, which is 1 to 3, optionally 1 to 2, 1 to 1.8, 1 to 1.6, or 1 to 1.4. A reasonable combination of the content A1% of the compound represented by Formula 1 and the content B1% of the cyclic carbonate compound helps to further improve the capacity retention of the secondary battery while improving the problems of poor power performance, increased safety hazards, and poor processing performance caused by thinning of the positive electrode current collector. And it can effectively avoid the following situations: when the contents of the compound represented by Formula 1 and the cyclic carbonate compound are both high, the internal resistance and gas production of the battery are high, which may affect the power performance and storage performance of the secondary battery; when the contents of the compound represented by Formula 1 and the cyclic carbonate compound are both low, the ionic conductivity of the non-aqueous electrolyte is low, and at the same time, there may not be enough compound represented by Formula 1 to form a passivation film on the surface of the positive electrode current collector and a low-impedance interface film on the surface of the positive electrode active material, thereby the processing performance of the positive electrode sheet may be poor, and the power performance, safety performance and cycle performance of the secondary battery may also deteriorate. [additive]

[0109] In some embodiments, the non-aqueous electrolyte may further include additives, such as halogen-substituted cyclic carbonate compounds, nitrile compounds, phosphazene compounds, aromatic hydrocarbons and halogenated aromatic hydrocarbon compounds, isocyanate compounds, acid anhydride compounds, sulfate compounds, sulfite compounds, sulfonate compounds, disulfonate compounds. This application has no particular restrictions on the types of these additives, as long as they do not undermine the purpose of this application. Optionally, the total mass percentage of these additives is less than 5%, more optionally less than 2.5%, based on the total mass of the non-aqueous electrolyte.

[0110] Optionally, in some embodiments, the non-aqueous electrolyte may further include fluoroethylene carbonate (FEC), the mass percentage of which is C1%, 0≤C1≤2.5, based on the total mass of the non-aqueous electrolyte. For example, C1 is 0, 0.10, 0.20, 0.50, 0.75, 1.0, 1.25, 1.50, 1.75, 2.0, 2.25, 2.50 or a range consisting of any of the above values. Optionally, 0<C1≤2.5, 0<C1≤2.25, 0<C1≤2.0, 0<C1≤1.75, 0<C1≤1.5, 0<C1≤1.25, 0<C1≤1.0, 0<C1≤0.75 or 0<C1≤0.5.

[0111] For secondary batteries, fluoroethylene carbonate can undergo a reductive decomposition reaction at a relatively high potential, forming a relatively flexible interfacial film on the surface of the negative electrode active material. It can also inhibit the reductive decomposition of organic solvents at lower potentials and inhibit the embedding of organic solvents into the negative electrode active material. Therefore, when fluoroethylene carbonate is contained in a non-aqueous electrolyte, the cycle performance of the secondary battery can be effectively improved. Furthermore, fluoroethylene carbonate is resistant to high-voltage oxidation, making it suitable for high-voltage positive electrode active materials, thereby further improving the energy density of the secondary battery.

[0112] In some embodiments, the content A1% of the compound represented by Formula 1 and the content C1% of the fluoroethylene carbonate further satisfy 0.25≤C1 / A1≤25. Alternatively, 0.5≤C1 / A1≤15, 0.5≤C1 / A1≤10, 0.5≤C1 / A1≤5, 0.5≤C1 / A1≤4, 0.5≤C1 / A1≤3, 0.5≤C1 / A1≤2.5, 0.5≤C1 / A1≤2, 0.5≤C1 / A1≤1.5, or 0.5≤C1 / A1≤1.0.

[0113] When the non-aqueous electrolyte contains fluoroethylene carbonate, it can effectively improve the cycle performance of the secondary battery. However, fluoroethylene carbonate easily decomposes and forms HF, which can destroy the positive electrode interface film, corrode the positive electrode active material, and increase the heat and gas production of the secondary battery. The compound shown in Formula 1 can be used as a stabilizer for the positive electrode active material. The B atoms in its structure have the function of interacting with the O atoms on the surface of the positive electrode active material, thereby stabilizing the crystal structure of the positive electrode active material and reducing the damage of HF to the crystal structure of the positive electrode active material. Therefore, the combined use of the compound shown in Formula 1 and fluoroethylene carbonate is conducive to fully utilizing the further improvement effect of fluoroethylene carbonate on the cycle performance of the secondary battery. In addition, the relationship between the content A1% of the compound shown in Formula 1 and the content C1% of fluoroethylene carbonate is reasonably controlled so that it satisfies 0.25≤C1 / A1≤25. The synergistic effect of the compound shown in Formula 1 and fluoroethylene carbonate can be fully utilized, thereby helping to further improve the cycle performance of the secondary battery while improving the problems such as poor power performance, increased safety hazards, and poor processing performance caused by the thinning of the positive electrode current collector. At the same time, fluoroethylene carbonate has a relatively high dielectric constant. By rationally controlling the relationship between the content A1% of the compound represented by Formula 1 and the content C1% of fluoroethylene carbonate so as to satisfy 0.25≤C1 / A1≤25, it is also possible to ensure that the anions and cations of the compound represented by Formula 1 form free ions and avoid anion-cation association. This, on the one hand, improves the ionic conductivity of the non-aqueous electrolyte and the cycle performance of the secondary battery, and on the other hand, increases the number of active lithium ions.

[0114] In some embodiments, the non-aqueous electrolyte may further include a dehydrating additive, which helps to reduce the water content of the non-aqueous electrolyte and reduce a series of side reactions caused by moisture, thereby reducing the gas production and heat production of the secondary battery, so that the secondary battery has better storage performance and safety performance. Optionally, in some embodiments, the dehydrating additive includes hexamethyldisilazane (HMDS), tris(trimethylsilyl)phosphate (TMSP) or a combination thereof. In addition to effectively reducing the moisture content of the non-aqueous electrolyte, these two dehydrating additives can also react with lithium hexafluorophosphate and form lithium difluorophosphate, which on the one hand reduces the decomposition of lithium hexafluorophosphate and the formation of HF, and on the other hand helps to further stabilize the positive electrode interface film and / or the negative electrode interface film, reduce the positive electrode interface impedance and / or the negative electrode interface impedance, thereby helping to further improve the power performance, storage performance and safety performance of the secondary battery.

[0115] In some embodiments, the weight percentage of the water removal additive is less than 2%, optionally 0.05% to 1%, more optionally 0.1% to 1%, based on the total weight of the non-aqueous electrolyte.

[0116] The non-aqueous electrolyte of the present application can be prepared according to conventional methods in the art. For example, the organic solvent, the lithium salt, and the additives can be uniformly mixed to obtain the non-aqueous electrolyte. The order of adding the materials is not particularly limited. For example, the lithium salt and the additives can be added to the organic solvent and mixed uniformly to obtain the non-aqueous electrolyte.

[0117] In the present application, the components and their contents in the non-aqueous electrolyte can be determined by methods known in the art. For example, they can be determined by gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), etc.

[0118] It should be noted that when testing the non-aqueous electrolyte of the present application, the non-aqueous electrolyte can be obtained from a secondary battery. An exemplary method for obtaining a non-aqueous electrolyte from a secondary battery includes the following steps: discharging the secondary battery to the discharge cutoff voltage (for safety reasons, the battery is generally fully discharged), then centrifuging it, and then taking an appropriate amount of the liquid obtained by centrifugation as the non-aqueous electrolyte. The non-aqueous electrolyte can also be obtained directly from the injection port of the secondary battery.

[0119] In the present application, the positive electrode active material layer includes a positive electrode active material, which can be a positive electrode active material commonly known in the art for use in secondary batteries. For example, the positive electrode active material can include at least one of a lithium transition metal oxide, an olivine-structured lithium-containing phosphate, and their respective modified compounds. Examples of lithium transition metal oxides include at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of olivine-structured lithium-containing phosphates include at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds. The present application is not limited to these materials; other conventionally known materials that can be used as positive electrode active materials for secondary batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.

[0120] In some embodiments, the positive electrode active material includes a molecular formula of Li a Ni b Co c Mn d Al e M f O g A h layered material, M represents a transition metal doping cation, A represents an oxygen doping anion, 0.8≤a≤1.2, 0≤b≤1, 0≤c≤1, 0≤d≤1, 0≤e≤1, 0≤f≤0.2, 0≤g≤2, 0≤h≤2, b+c+d+e+f=1, g+h=2.

[0121] The molecular formula is Li a Ni b Co c Mn d Al e M f O g A h The layered material can be optionally modified by doping with M cations, doping with A anions, or doping with both M cations and A anions. The crystal structure of the layered material obtained after doping is more stable, lattice oxygen is not easy to precipitate, and transition metal ions are not easy to escape, thereby reducing a series of side reactions caused by them, thereby further improving the safety performance and electrochemical performance of the secondary battery, such as cycle performance, kinetic performance, etc.

[0122] In some embodiments, M is selected from at least one of Si, Ti, Mo, V, Ge, Se, Zr, Nb, Ru, Pd, Sb, Ce, Te, and W.

[0123] In some embodiments, A is selected from at least one of F, N, P and S. Optionally, A is selected from F. After F doping modification, Li a Ni b Co c Mn d Al e M f O g A h The crystal structure is more stable, lattice oxygen is not easy to precipitate, and transition metal ions are not easy to escape, thereby enabling the secondary battery to have better safety performance, cycle performance and kinetic performance.

[0124] The values ​​of a, b, c, d, e, f, g, and h satisfy the following conditions: a Ni b Co c Mn d Al e M f O g A h Maintain electrical neutrality.

[0125] In some embodiments, 0<b<0.98. Alternatively, 0.50≤b<0.98, 0.55≤b<0.98, 0.60≤b<0.98, 0.65≤b<0.98, 0.70≤b<0.98, 0.75≤b<0.98 or 0.80≤b<0.98.

[0126] In some embodiments, c=0.

[0127] In some embodiments, 0<c≤0.20. Optionally, 0<c≤0.15, 0<c≤0.10, 0<c≤0.09, 0<c≤0.08, 0<c≤0.07, 0<c≤0.06, 0<c≤0.05, 0<c≤0.04, 0<c≤0.03, 0<c≤0.02 or 0<c≤0.01. Cobalt is present in low concentrations in the earth's crust, is difficult to mine and is expensive, so low cobalt or cobalt-free materials are an inevitable development trend for positive electrode active materials. However, cobalt contributes greatly to the lithium ion diffusion rate of positive electrode active materials. Low cobalt or cobalt-free materials will reduce the lithium ion diffusion rate of positive electrode active materials and affect the cycle performance of secondary batteries. Researchers have been committed to improving the lithium ion diffusion rate of low cobalt or cobalt-free positive electrode active materials, but there is currently no good solution.

[0128] During the research process, the inventors of the present application also unexpectedly discovered that the B atom in the compound structure shown in Formula 1 easily combines with the O atom in the positive electrode active material, reducing the charge transfer impedance of the positive electrode active material, thereby reducing the diffusion resistance of lithium ions in the bulk phase of the positive electrode active material. Therefore, the low-cobalt or cobalt-free positive electrode active material can have a significantly improved lithium ion diffusion rate, and the lithium ions in the bulk phase of the low-cobalt or cobalt-free positive electrode active material can be replenished to the surface in a timely manner, avoiding excessive lithium removal from the surface of the low-cobalt or cobalt-free positive electrode active material, thereby stabilizing the crystal structure of the low-cobalt or cobalt-free positive electrode active material. Since the crystal structure of the low-cobalt or cobalt-free positive electrode active material of the present application is more stable, it can greatly reduce the probability of problems such as the structural properties, chemical properties or electrochemical properties of the positive electrode active material becoming unstable due to excessive lithium removal from the surface of the low-cobalt or cobalt-free positive electrode active material, such as the problem of irreversible distortion and increased lattice defects in the positive electrode active material.

[0129] In some embodiments, d=0 and 0<e<0.50. Alternatively, d=0 and 0<e≤0.45, d=0 and 0<e≤0.40, d=0 and 0<e≤0.35, d=0 and 0<e≤0.30, d=0 and 0<e≤0.25, d=0 and 0<e≤0.20, d=0 and 0<e≤0.15, or d=0 and 0<e≤0.10.

[0130] In some embodiments, e=0 and 0<d<0.50. Alternatively, e=0 and 0<d≤0.45, e=0 and 0<d≤0.40, e=0 and 0<d≤0.35, e=0 and 0<d≤0.30, e=0 and 0<d≤0.25, e=0 and 0<d≤0.20, e=0 and 0<d≤0.15, or e=0 and 0<d≤0.10.

[0131] In some embodiments, 0<d<0.50 and 0<e<0.50. Alternatively, 0<d≤0.30 and 0<e≤0.10.

[0132] In some embodiments, g=2, h=0.

[0133] In some embodiments, g=0, h=2.

[0134] In some embodiments, 0<g<2, 0<h<2, and g+h=2.

[0135] As an example, the molecular formula is Li a Ni b Co c Mn d Al e M f O g A hLayered materials include but are not limited to LiNi 0.7 Mn 0.3 O2、LiNi 0.69 Co 0.01 Mn 0.3 O2、LiNi 0.68 Co 0.02 Mn 0.3 O2、LiNi 0.65 Co 0.05 Mn 0.3 O2、LiNi 0.63 Co 0.07 Mn 0.3 O2、LiNi 0.61 Co 0.09 Mn 0.3 At least one of O2.

[0136] Li a Ni b Co c Mn d Al e M f O g A h The preparation can be performed according to conventional methods in the art. An exemplary preparation method is as follows: a lithium source, a nickel source, a cobalt source, a manganese source, an aluminum source, an M element precursor, and an A element precursor are mixed and sintered. The sintering atmosphere can be an oxygen-containing atmosphere, such as air or an oxygen atmosphere. The O2 concentration of the sintering atmosphere is, for example, 70% to 100%. The sintering temperature and sintering time can be adjusted according to actual conditions.

[0137] As an example, the lithium source includes, but is not limited to, at least one of lithium oxide (Li2O), lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium carbonate (Li2CO3), and lithium nitrate (LiNO3). As an example, the nickel source includes, but is not limited to, at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate, and nickel acetate. As an example, the cobalt source includes, but is not limited to, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate, and cobalt acetate. As an example, the manganese source includes, but is not limited to, at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, and manganese acetate. As an example, the aluminum source includes, but is not limited to, at least one of aluminum sulfate, aluminum nitrate, aluminum chloride, aluminum oxalate, and aluminum acetate. As an example, the M element precursor includes, but is not limited to, at least one of an oxide, a nitric acid compound, a carbonate compound, a hydroxide compound, and an acetate compound of the M element. As an example, the precursor of element A includes but is not limited to at least one of ammonium fluoride, lithium fluoride, hydrogen fluoride, ammonium chloride, lithium chloride, hydrogen chloride, ammonium nitrate, ammonium nitrite, ammonium carbonate, ammonium bicarbonate, ammonium phosphate, phosphoric acid, ammonium sulfate, ammonium bisulfate, ammonium bisulfite, ammonium sulfite, ammonium bisulfide, hydrogen sulfide, lithium sulfide, ammonium sulfide and elemental sulfur.

[0138] In some embodiments, based on the total mass of the positive electrode active material layer, the molecular formula is Li a Ni b Co c Mn d Al e M f O g A h The content of the layered material is 80% to 99%. For example, the molecular formula is Li a Ni b Co c Mn d Al e M f O g A h The content of the layered material can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or any range thereof. a Ni b Co c Mn d Al e M f O g A hThe content of the layered material is 85% to 99%, 90% to 99%, 95% to 99%, 80% to 98%, 85% to 98%, 90% to 98%, 95% to 98%, 80% to 97%, 85% to 97%, 90% to 97% or 95% to 97%.

[0139] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. This application does not particularly limit the type of the positive electrode conductive agent. By way of example, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.

[0140] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode binder. This application does not particularly limit the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%.

[0141] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0142] In the present application, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material can be a negative electrode active material for secondary batteries that is well known in the art. As an example, the negative electrode active material includes but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material. The present application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials for secondary batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0143] In some embodiments, the negative electrode active material layer may optionally include a negative electrode conductive agent. This application does not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is less than 5% based on the total mass of the negative electrode active material layer.

[0144] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. For example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), a water-soluble unsaturated resin SR-1B, a water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is less than 5% based on the total mass of the negative electrode active material layer.

[0145] In some embodiments, the negative electrode active material layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is less than 2% based on the total weight of the negative electrode active material layer.

[0146] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may be selected from at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0147] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring until uniformly distributed. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0148] In this application, the separator is disposed between the positive electrode and the negative electrode, primarily to prevent short circuits between the positive and negative electrodes while allowing lithium ions to pass through. This application does not particularly limit the type of separator; any known porous separator with good chemical and mechanical stability may be used.

[0149] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different.

[0150] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0151] The present application has no particular restrictions on the shape of the secondary battery, which can be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0152] In some embodiments, as Figure 2 As shown, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The non-aqueous electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.

[0153] The preparation method of the secondary battery of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and a non-aqueous electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, separator, and negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process. The electrode assembly is placed in an outer packaging, dried, and then injected with a non-aqueous electrolyte. The secondary battery is then vacuum packaged, allowed to stand, formed, and shaped to obtain the secondary battery.

[0154] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0155] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of secondary batteries 5 can be arranged in sequence along the length direction of the battery module 4. Of course, they can also be arranged in any other manner. Further, the plurality of secondary batteries 5 can be fixed by fasteners.

[0156] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0157] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0158] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, a battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 is used to cover the lower box body 3 and form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0159] The embodiments of the present application also provide an electric device, which includes at least one of the secondary battery, battery module or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0160] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0161] Figure 6 The figure is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module can be used.

[0162] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source. Example

[0163] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.

[0164] The secondary batteries of the examples and comparative examples were prepared according to the following method.

[0165] Preparation of positive electrode

[0166] The positive electrode active material LiNi 0.65 Co 0.05 Mn 0.3 O2, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are thoroughly stirred in an appropriate amount of solvent NMP at a mass ratio of 97.5:1.4:1.1 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet. The thickness of the positive electrode current collector Hμm, the elongation at break Q%, and the compacted density of the positive electrode active material layer P g / cm 3 The specific ranges are shown in Table 1 and Table 3 respectively.

[0167] Preparation of negative electrode sheet

[0168] The negative electrode active material graphite, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na), and conductive agent carbon black (Super P) are fully stirred and mixed in an appropriate amount of solvent deionized water at a mass ratio of 96.2:1.8:1.2:0.8 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.

[0169] Isolation film

[0170] A porous polyethylene (PE) film is used as the separator.

[0171] Preparation of non-aqueous electrolyte

[0172] According to the compositions shown in Tables 1 and 3, a cyclic carbonate compound, a chain carbonate compound, and a carboxylate compound are uniformly mixed to obtain an organic solvent. Subsequently, according to the compositions shown in Tables 1 and 3, the compound shown in Formula 1, fluoroethylene carbonate (FEC), lithium hexafluorophosphate (LiPF6), and lithium bis(fluorosulfonyl)imide (LiFSI) are added to the organic solvent and mixed uniformly to obtain a non-aqueous electrolyte. In Tables 1 and 3, the content of each component is based on the total mass of the non-aqueous electrolyte, and " / " indicates that the corresponding component is not added.

[0173] Preparation of secondary batteries

[0174] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with a non-aqueous electrolyte. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.

[0175] Test section

[0176] (1) Secondary battery mass energy density test

[0177] At 25°C, charge the secondary battery at a constant current of 0.33C to 4.25V, then continue constant voltage charging until the current reaches 0.05C. After the secondary battery rests for 5 minutes, discharge it at a constant current of 0.33C to 2.8V to obtain the discharge energy. The mass energy density (Wh / Kg) of a secondary battery is calculated as: discharge energy / mass of the secondary battery.

[0178] (2) Secondary battery power performance test

[0179] At 25°C, charge the secondary battery at a constant current of 0.1C to 4.25V. Continue constant voltage charging until the current reaches 0.05C, at which point the secondary battery is fully charged. Discharge the secondary battery at a constant current of 1C for approximately 30 minutes, adjusting the state of charge to 50% SOC. The voltage at this point is recorded as V0. Discharge the secondary battery at a current of 4C, I1, for 30 seconds, sampling at 0.1 seconds. The voltage at the end of discharge is recorded as V1. The internal resistance of the secondary battery, DCR, = (V0 - V1) / I1. The lower the internal resistance of the secondary battery, the better the power performance.

[0180] (3) Secondary battery hot box safety performance test

[0181] At 25°C, charge the secondary battery at a constant current of 0.1C to 4.25V, and continue to charge at a constant voltage until the current reaches 0.05C, at which point the secondary battery is fully charged. Place the fully charged secondary battery in a well-sealed high-temperature box, heat it to 100°C at a rate of 5°C / min, hold it for 1 hour, then heat it to 105°C at a rate of 5°C / min, hold it for 30 minutes, then heat it up at a rate of 5°C / min, and hold it for 30 minutes each time the temperature rises by 5°C, until the secondary battery fails. Record the highest temperature T before the secondary battery fails. max . T max The higher it is, the better the hot box safety performance of the secondary battery.

[0182] (4) Secondary battery cycle performance test

[0183] At 45°C, charge the secondary battery at a constant current of 1C to 4.25V. Continue constant voltage charging until the current reaches 0.05C. At this point, the secondary battery is fully charged. Record the charge capacity at this point, which is the charge capacity of the first cycle. After the secondary battery rests for 5 minutes, discharge it at a constant current of 1C to 2.8V. This constitutes one charge-discharge cycle. Record the discharge capacity at this point, which is the discharge capacity of the first cycle. Perform the cyclic charge-discharge test on the secondary battery according to the above method, and record the discharge capacity after each cycle. Capacity retention (%) of the secondary battery after 600 cycles at 45°C = discharge capacity after 600 cycles / discharge capacity after the first cycle × 100%.

[0184] (5) Secondary battery storage performance test

[0185] At 60°C, charge the secondary battery at a constant current of 1C to 4.25V. Continue constant voltage charging until the current reaches 0.05C. At this point, measure the volume of the secondary battery using the water displacement method and record it as V0. Place the secondary battery in a constant temperature chamber at 60°C for 30 days. After removal, measure the volume of the secondary battery using the water displacement method and record it as V1. The volume expansion rate (%) of the secondary battery after 30 days of storage at 60°C = [(V1 - V0) / V0] × 100%.

[0186] Table 1 shows the parameters of the positive electrode sheets and non-aqueous electrolytes of Examples 1-1 to 1-33 and Comparative Examples 1-1 to 1-4. Table 2 shows the test results of Examples 1-1 to 1-33 and Comparative Examples 1-1 to 1-4 obtained according to the above performance test method.

[0187] Table 3 shows the parameters of the positive electrode sheets and non-aqueous electrolytes of Examples 2-1 to 2-32 and Comparative Examples 2-1 to 2-3. Table 4 shows the test results of Examples 2-1 to 2-32 and Comparative Examples 2-1 to 2-3 obtained according to the above performance test method.

[0188] From the test results in Table 1 and Table 2, it can be seen that in the secondary battery with a thinned positive electrode current collector, when the non-aqueous electrolyte contains the compound represented by Formula 1 and its content A1% is related to the thickness of the positive electrode current collector Hμm, the elongation at break of the positive electrode current collector Q% and the compaction density of the positive electrode active material layer P g / cm 3 When A1 / H is 0.0015 to 0.20, Q+A1 is 1 to 4 and P / A1 is 2 to 340, the secondary battery can simultaneously have higher energy density, lower internal resistance, higher hot box safety performance, higher capacity retention rate and lower volume expansion rate.

[0189] Based on the test results of Examples 1-1 to 1-10 and Comparative Example 1-2, it can be seen that when A1 / H is less than 0.0015 and / or P / A1 is greater than 340, there is not enough compound represented by Formula 1 to react with Al 3+ Bonding and forming a passivation film on the surface of the positive electrode current collector and a low-impedance interface film on the surface of the positive electrode active material, compared with comparative example 1-1, does not effectively improve the negative impact of thinning the positive electrode current collector on power performance and safety performance, and the increase in the capacity retention rate of the secondary battery is also limited.

[0190] Based on the test results of Examples 1-1 to 1-10 and Comparative Examples 1-3 to 1-4, it can be seen that when Q+A1 is greater than 4, A1 / H is greater than 0.20 and / or P / A1 is less than 2, excessive amount of the compound represented by Formula 1 will cause the positive electrode interface impedance and / or the negative electrode interface impedance to increase instead of decrease, thereby resulting in a high internal resistance and poor capacity retention of the secondary battery; although the compound represented by Formula 1 can contribute some active lithium ions and slightly increase the energy density of the secondary battery, the oxidative decomposition of the anions leads to a high gas production inside the battery and a significant deterioration in the safety performance of the hot box.

[0191] From the test results in Table 3 and Table 4, it can be seen that in the secondary battery with a thinned positive electrode current collector, when the non-aqueous electrolyte contains the compound represented by Formula 1 and its content A1% is related to the thickness of the positive electrode current collector Hμm, the elongation at break of the positive electrode current collector Q% and the compaction density of the positive electrode active material layer P g / cm 3When A1 / H is 0.0015 to 0.20, Q+A1 is 1 to 4 and P / A1 is 2 to 340, the secondary battery can simultaneously have higher energy density, lower internal resistance, higher hot box safety performance, higher capacity retention rate and lower volume expansion rate.

[0192] Based on the test results of Examples 2-1 to 2-9 and Comparative Example 2-2, it can be seen that when A1 / H is less than 0.0015, there is not enough compound represented by Formula 1 to react with Al 3+ It bonds and forms a passivation film on the surface of the positive electrode current collector and a low-impedance interface film on the surface of the positive electrode active material. Therefore, compared with Comparative Example 2-1, the negative impact of thinning the positive electrode current collector on power performance and safety performance is not effectively improved, and the increase in the capacity retention rate of the secondary battery is also limited.

[0193] Based on the test results of Examples 2-1 to 2-9 and Comparative Example 2-3, it can be seen that when A1 / H is greater than 0.20, P / A1 is less than 2 and Q+A1 is greater than 4, excessive amount of the compound represented by Formula 1 will cause the positive electrode interface impedance and / or the negative electrode interface impedance to increase instead of decrease, thereby resulting in a high internal resistance and poor capacity retention of the secondary battery; although the compound represented by Formula 1 can contribute some active lithium ions and slightly increase the energy density of the secondary battery, the oxidative decomposition of the anions leads to a high gas production inside the battery and a significant deterioration in the safety performance of the hot box.

[0194] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery comprising a positive electrode sheet and a non-aqueous electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector, in, The non-aqueous electrolyte includes a compound represented by Formula 1, wherein X and Y each independently represent a fluorine atom, or at least one of the group consisting of the following groups which are partially or fully fluorinated: a C1-C10 alkyl group, a C2-C10 alkenyl group, a C2-C10 alkynyl group, a C6-C8 aryl group, a C1-C10 alkoxy group, a C2-C10 alkenyloxy group, a C2-C10 alkynyloxy group, a C6-C8 aryloxy group, and at least one of X and Y represents a fluorine atom; The non-aqueous electrolyte includes a first lithium salt, the first lithium salt includes a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, the mass percentage of the lithium hexafluorophosphate is A2%, the mass percentage of the lithium bis(fluorosulfonyl)imide is A3%, both based on the total mass of the non-aqueous electrolyte, A2 is 6 to 14, A3 is greater than 0, and A3 / A2 is less than 0.8; The thickness of the positive electrode current collector is H μm, where H is 4 to 14.

2. The secondary battery according to claim 1, wherein A3 / A2 is 0.01 to 0.8, optionally 0.05 to 0.6; and / or, A2 is 8 to 12; and / or, H is 9 to 14.

3. The secondary battery according to any one of claims 1 to 2, wherein: A3 is greater than 0 and less than or equal to 5, and can be selected from 0.1 to 2.

5.

4. The secondary battery according to any one of claims 1 to 3, wherein: The non-aqueous electrolyte further includes a second lithium salt, the second lithium salt includes at least one of lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium difluorophosphate, lithium difluorobisoxalate phosphate and lithium tetrafluorooxalate phosphate, the total mass percentage of the second lithium salt in the non-aqueous electrolyte is A4%, based on the total mass of the non-aqueous electrolyte, Optionally, A4 is below 5, more preferably below 2.

5. The secondary battery according to claim 4, wherein The second lithium salt includes lithium difluorophosphate, Optionally, the mass ratio α of the lithium difluorophosphate to the lithium hexafluorophosphate is 0.01 to 0.15, more preferably 0.01 to 0.

1.

6. The secondary battery according to any one of claims 1 to 5, wherein: Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and A2 / A1 is 5 to 650, and optionally 15 to 300.

7. The secondary battery according to any one of claims 1 to 6, wherein: Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and A1 is 0.02 to 1.8, and optionally 0.02 to 0.

5.

8. The secondary battery according to any one of claims 1 to 7, wherein: Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and A1 / H is 0.0015 to 0.20, optionally 0.002 to 0.05, and more optionally 0.01 to 0.

05.

9. The secondary battery according to any one of claims 1 to 8, wherein: The compaction density of the positive electrode active material layer is P g / cm 3 , P is 3.2 to 3.7, optionally 3.4 to 3.

7.

10. The secondary battery according to any one of claims 1 to 9, wherein: The compaction density of the positive electrode active material layer is P g / cm 3 , based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and P / A1 is 2 to 340, optionally 5 to 100.

11. The secondary battery according to any one of claims 1 to 10, wherein: The positive electrode current collector has a fracture elongation of Q%, wherein Q is 0.5 to 3.5, and optionally 1.5 to 3.

5.

12. The secondary battery according to any one of claims 1 to 11, wherein: The elongation at break of the positive electrode current collector is Q%, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and Q+A1 is 1 to 4, optionally 1.5 to 3.5, and more optionally 2.0 to 3.

5.

13. The secondary battery according to any one of claims 1 to 12, wherein: The compaction density of the positive electrode active material layer is P g / cm 3 The elongation at break of the positive electrode current collector is Q%, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and the secondary battery satisfies: H is 11 to 14, A1 / H is 0.005 to 0.15, Q+A1 is 1 to 4, and P / A1 is 2 to 100; Optionally, A1 / H is 0.005 to 0.1, Q+A1 is 1.5 to 3.5, and P / A1 is 5 to 75.

14. The secondary battery according to any one of claims 1 to 12, wherein: The compaction density of the positive electrode active material layer is P g / cm 3 The elongation at break of the positive electrode current collector is Q%, based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound represented by Formula 1 is A1%, and the secondary battery satisfies: H is 4 to 11, A1 / H is 0.006 to 0.1, Q+A1 is 1 to 4, and P / A1 is 2 to 100; Optionally, H is 9 to 11, A1 / H is 0.01 to 0.05, Q+A1 is 1.5 to 3.5, and P / A1 is 5 to 75.

15. The secondary battery according to any one of claims 1 to 14, wherein: The non-aqueous electrolyte further comprises a cyclic carbonate compound, the mass percentage content of the cyclic carbonate compound is B1%, based on the total mass of the non-aqueous electrolyte, B1 is 0.5 to 20, optionally 15 to 18.

16. The secondary battery according to any one of claims 1 to 15, wherein: The non-aqueous electrolyte also includes a cyclic carbonate compound, the mass percentage of the cyclic carbonate compound is B1%, and the mass percentage of the compound represented by Formula 1 is A1%, both based on the total mass of the non-aqueous electrolyte, B1 / 20+A1 is 1 to 3, optionally 1 to 2.

17. The secondary battery according to any one of claims 15 to 16, wherein: The cyclic carbonate compound includes at least one of ethylene carbonate, propylene carbonate, vinylene carbonate, and vinylethylene carbonate.

18. The secondary battery according to any one of claims 1 to 17, wherein: The non-aqueous electrolyte further includes a chain carbonate compound, the mass percentage of the chain carbonate compound is B2%, and B2 is 45 to 80, based on the total mass of the non-aqueous electrolyte.

19. The secondary battery according to any one of claims 1 to 18, wherein: The non-aqueous electrolyte further comprises a carboxylate compound, the mass percentage of the carboxylate compound is B3%, and B3 is 2 to 15.

20. The secondary battery according to any one of claims 1 to 19, wherein: The non-aqueous electrolyte also includes additives, which include at least one of halogen-substituted cyclic carbonate compounds, nitrile compounds, phosphazene compounds, aromatic hydrocarbons and halogenated aromatic hydrocarbon compounds, isocyanate compounds, acid anhydride compounds, sulfate compounds, sulfite compounds, sulfonate compounds, and disulfonate compounds, and the total mass percentage of the additives is less than 5%, based on the total mass of the non-aqueous electrolyte.

21. The secondary battery according to any one of claims 1 to 20, wherein: The non-aqueous electrolyte further includes fluoroethylene carbonate, the mass percentage of which is C1%, based on the total mass of the non-aqueous electrolyte, 0<C1≤2.5, optionally, 0<C1≤2.

0.

22. The secondary battery according to any one of claims 1 to 21, wherein: The non-aqueous electrolyte also includes fluoroethylene carbonate, whose mass percentage is C1%, and the mass percentage of the compound represented by Formula 1 is A1%, both based on the total mass of the non-aqueous electrolyte, 0.25≤C1 / A1≤25, optionally, 0.5≤C1 / A1≤10.

23. The secondary battery according to any one of claims 1 to 22, wherein: The non-aqueous electrolyte further includes a water-removing additive, wherein the water-removing additive includes at least one of hexamethyldisilazane and tris(trimethylsilyl)phosphate. Optionally, the mass percentage of the water removal additive is less than 2%, more preferably 0.05% to 1%, based on the total mass of the non-aqueous electrolyte.

24. The secondary battery according to any one of claims 1 to 23, wherein: X and Y satisfy one of the following conditions (1) to (3): (1) X and Y both represent fluorine atoms; (2) one of X and Y represents a fluorine atom, and the other represents at least one of the group consisting of a partially fluorinated or fully fluorinated C1-C5 alkyl group, a C2-C5 alkenyl group, a C2-C5 alkynyl group, a phenyl group, a phenoxy group, a C1-C5 alkoxy group, a C2-C5 alkenyloxy group, and a C2-C5 alkynyloxy group; (3) One of X and Y represents a fluorine atom and the other represents at least one of the group consisting of the following partially or fully fluorinated groups: methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, vinyl, propenyl, allyl, butadienyl, ethynyl, propynyl, phenyl, methoxy, ethoxy, propoxy, vinyloxy, propenyloxy, ethynyloxy, propynyloxy and phenoxy.

25. The secondary battery according to any one of claims 1 to 24, wherein: The compound represented by Formula 1 includes at least one of the following compounds:

26. The secondary battery according to any one of claims 1 to 25, wherein: The positive electrode current collector is made of aluminum foil or aluminum alloy foil; and / or, The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a lithium transition metal oxide, an olivine-structured lithium-containing phosphate, and modified compounds thereof.

27. A battery module comprising the secondary battery according to any one of claims 1 to 26.

28. A battery pack comprising the secondary battery according to any one of claims 1 to 26 and the battery module according to claim 27.

29. An electrical device comprising at least one of the secondary battery according to any one of claims 1 to 26, the battery module according to claim 27, and the battery pack according to claim 28.

Citation Information

Patent Citations

  • High-voltage electrolyte for lithium ion battery

    CN106159328A

  • Electrolyte and lithium ion battery

    CN108183260A

  • 18650 fast charge type lithium ion battery and preparation method thereof

    CN108400376A

  • Additive used for lithium ion battery electrolyte and electrolyte and lithium ion battery

    CN109524715A

  • Long-cycle lithium ion electrolyte and battery

    CN109659609A